REPUTATION MANAGEMENT IN SOCIAL NETWORKS – STUDY OF THE TOP ORGANISATIONS IN INDIA - Antony Raj J.M (International Journal of Psychosocial Rehabilitation, 2020)
Management of the social network of an organization always involves time and money and we normally assume that large organisations would have clear cut strategies when compared to midsize and smaller organizations. This research study tests this assumption based on a study of top 105 Indian companies (35 Large cap, 35 middle cap, 35 small cap) by market capitalization. The results of this research supported that large cap organisations were much more responsive and also responded quickly when compared to mid-cap and small cap organisations.We very well know the effect of non-responsiveness on the brand image of an organization .overall from the study we can see that most of the firms in India are not monitoring, integrating or leveraging social media management adequately.